Upaya Pemerintah dalam mengembangkan UMKM melalui Program Car Free Day DI Kota Kraksaan - Sucahyo, Imam; Hidayatullah, M. Rizky; Amrullah, M. Januar; Karimah, Zahrotul; Musthofa, Ahmad; Aisyah, Siti (DIALEKTIKA: Jurnal Ekonomi dan Ilmu Sosial, 2023)
The purpose of this study is to find out the efforts of the Kraksaan City government, Proboliggo Regency in developing MSMEs through the Car Free Day (CFD) program. Based on the discussion of research results regarding the objectives, including knowing the physical condition of the Car Free Day program, and the influence of the Car Free Day program. In this study the authors used qualitative methods where the results of the research did not use elements of statistics or calculations. And the results of this study are in the form of narratives, interviews and documentation. It can be concluded from the results of the research that the Car Free Day program is held by the government with the main objective of increasing MSME income, another objective is as a venue for local community talent and creativity, and as entertainment for people who come to visit, while the facilities provided by the Probolinggo Regency government to traders only provide facilities in the form of roads as a place for traders to sell, the existence of these facilities aims to help MSMEs when trading.